Waktu Inseminasi Buatan yang Tepat pada Sapi Bali dan Kadar Progesteron pada Sapi Bunting (THE OPTIMUM TIME FOR ARTIFICIAL INSEMINATION IN BALI CATTLE AND THE PROGESTERONE LEVEL IN PREGNANT COW) - Pemayun, Tjok Gde Oka; Trilaksana, I Gusti Ngurah Bagus; Budiasa, Made Kota (Jurnal Veteriner; Vol 15 No 3 (2014), 2014)
This study aims were to determine the proper time for insemination and the progesterone level ofpregnant Bali cattle. Complete randomized design method was used in this study. The study consisted ofthree treatment groups i.e. Group I, animals were inseminated at 0 hour (on estrus), group II, inseminatedat 12 h post-estrus and group III inseminated at 24 h post-estrus. Estrus was observed two times a day ie.in the morning (6:00 to 8:00 am) and afternoon (16:00 to 18:00 pm) which was characterized by transparentvaginal discharge. The results showed that the highest percentage of pregnancy occurred when the cattlewere inseminated at 24 h post-estrus (100%), however, statistically this was not significant different (P>0.05) to animals that were inseminated at 12 h post-estrus (75%). Moreover, no pregnancy (0%) wasobserved in cattle that were inseminated at estrus. The progesterone level of pregnant bali cattle increasedas the period of gestation increased, being 15.43 ± 0.50 ng/mL at 30 days of gestation, 17.16 ± 0.34 ng/mLat 60 days of gestation and 20.78 ± 0.59 ng/mL at 90 days of gestation. In conclusion, the best time forinsemination in Bali cattle is at 24 h post-estrus and progesterone level seems to increase as the older thegestation period.
Keywords: artificial insemination, progesterone, pregnancy diagnosis, Bali cattle